International Monetary Fund Annual Report 2017 : Promoting Inclusive Growth. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2017)
During the past financial year, the IMF's 189 member countries faced a number of pressing challenges. IMF work on these challenges-slower trade, declining productivity, gender inequality, inclusive growth, and debt management-is a central focus of this 2017 Annual Report.